Mapping, Triggering, Scoring, and Procedural Paradigms of Machine Listening Application in Live-Electronics Compositions - Oliveira, Vinicius César; Padovani, José Henrique (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2021)
Since the advent of real-time computer music environments, composers have increasingly incorporated DSP analysis, synthesis, and processing algorithms in their creative practices. Those processes became part of interactive systems that use real-time computational tools in musical compositions that explore diverse techniques to generate, spatialize, and process instrumental/vocal sounds. Parallel to the development of these tools and the expansion of DSP methods, new techniques focused on sound/musical information extraction became part of the tools available for music composition. In this context, this article discusses the creative use of Machine Listening and Musical Information Retrieval techniques applied in the composition of live-electronics works. By pointing out some practical applications and creative approaches, we aim to circumscribe, in a general way, the strategies for employing Machine Listening and Music Information Retrieval techniques observed in a set of live-electronics pieces, categorizing four compositional approaches: namely, mapping, triggering, scoring, and procedural paradigms of application of machine listening techniques in the context of live-electronics music compositions.